Deskripsi Korban Mati Akibat Jejas di Leher Yang Diperiksa di RSUD Dr. Moewardi Tahun 2015-2021 - Novianto Adi Nugroho; Haniifah, Firda Luthfiyyatul; Suwandono, Adji (Fakultas Kedokteran, Universitas Sebelas Maret, 2022)
Introduction: Surakarta has a population growth rate 0.43%, the high population density can cause population problems homicides, accidents, and hanging themselves. This case can be proven by the discovery of neck injuries due to strangulation. This study was conducted to find out about the description of victims who died due to neck injuries in 2015-2021. Methods: This study used a descriptive observational method from Visum et Repertum with the population in the form of all forensic pathology case due to neck injuries which were examined at Dr. Moewardi hospital in 2015-2021. The sampling technique in this study was purposive sampling that met the inclusion and exclusion criteria. Results: From the VeR Dr. Moewardi hospital in 2015-2021 obtained as many as 28 cases of forensic pathology due to neck injuries with the description: (1) tilted injury shape 57.14%, horizontal 39.29%, crescent moon 3.57%; (2) blunt hardness 96.43%, sharp 3.57%; (3) submission of requests for VeR from the Surakarta Police 53.57%, Sukoharjo 14.29%, Boyolali 14.29%, Wonogiri 7.14%, Sragen 7.14%, Karanganyar 3.57%; (4) external examination 57.14%, autopsy 42.86%; (5) suicide 53.57%, homicide 32.14%, accident 7.14%; (6) age <15 years 7.14%, 15-64 years 78.57%, >64 years 10.71%; (7) male 67.86%, female 32.14%; (8) private employment 67.86%, students 10.71%, housewives 7.14%, not working 7.14% Conclusion: From this research, the most results were in the form of slanted neck injuries, violence due to blunt objects, requests for VeR from the Surakarta police, external examination, the method of death was suicide, victims of productive age, men, and private workers.